Analysis of Dynamic Characteristics for a Rotor System with Pedestal Looseness - Hui Ma; Xueyan Zhao; Yunnan Teng; Bangchun Wen (Shock and Vibration)
This paper presents a finite element model of a rotor system with pedestal looseness stemming from a loosened bolt and analyzes the effects of the looseness parameters on its dynamic characteristics. When the displacement of the pedestal is less than or equal to the looseness clearance, the motion of the rotor varies from period-one through period-two and period-three to period-five with the decreasing of stiffness of the non-loosened bolts. The similar bifurcation phenomenon can be also observed during the increasing process of the rotational speed. But the rotor motion is from period-six through period-three to period-four with the decreasing of the foundation stiffness. When the stiffness of the foundation is small and the displacement of pedestal is greater than the looseness clearance, the response of the rotor exhibits period-one and high order harmonic components with the decreasing of looseness clearance, such as 2X, 3X etc. However, when the stiffness of the foundation is great, the spectrum of the response of the rotor will be from combined frequency components to the continuous spectrum with the decreasing of the looseness clearance.